Predicting glioblastoma response to bevacizumab through marker profiling? - Keßler, Tobias (Neuro-Oncology, 2016)
Bevacizumab is a humanized monoclonal antibody directed against the vascular endothelial growth factor (VEGF). It has been approved for antiangiogenic treatment
Gesehen am 11.05.2020